Formulation of Nutraceutical Jelly Candy from a Combination of Cucurbita moschata Puree and Averrhoa carambola Juice as Antioxidant - Soraya, Alya Fajrina; Kawareng, Andi Tenri; Agustina, Risna (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Nutraceutical candy jellies are gaining popularity as a potential approach to deliver antioxidants in a palatable form. This study investigated the antioxidant activity of Cucurbita moschata puree combined with Averrhoa carambola juice, formulated into jelly candies. Design-Expert software V.13 was used to optimize the jelly candy base formula. The combined C. moschata puree and A. carambola juice exhibited strong antioxidant activity (IC50 = 29.580 ppm) at variation V1. The optimal base formula B3 consisted of 12% gelatin and 4% carrageenan. The formulated jelly candy possessed very strong antioxidant activity (IC50 = 44.771 ppm). These findings suggest the potential of C. moschata puree and A. carambola juice as ingredients in functional jelly candies.